Ecodesign: estudo de caso em uma indústria de móveis de escritório - Juan Carlos Claros Garcia (2007)
Research that gathers Ecodesign tools and concepts such as product environmental parameters, environmental impact assessment, checklists, design for X techniques, and Ecodesign strategies, bearing in mind the elaboration of an Ecodesign method applicable to office furniture. In the same manner, environmental characteristics of therelationship between furniture requirements in the offices and furniture design are discussed, searching for Ecodesign intervention opportunities. A case study research in a medium-sized office furniture manufacturer was realized, where its productive processes, characteristic features, design practices, representative products, relationshipswith its suppliers and purchasers, among other aspects, were observed, searching for instruments for the elaboration of the Ecodesign method. Parallel to the elaboration of the method, the environmental assessment of a workstation system produced by the researched manufacturer was realized, and environmental parameters in current literature were confronted with it. Specific Ecodesign strategies for furniture were alsoinvestigated, where some specific office furniture strategies were found. For the method elaboration, those strategies were classified accordingly with the Ecodesign parameters. The findings indicate that Ecodesign implementation in medium-sized office furniture manufacturers is more applicable as of the introduction of product improvement and redesigntechniques, aspects that get along with the designers intervention possibilities. On the other hand, it was observed that advances in information technology and changes in office work influence the design of furniture, favoring the environmental office furniture performance through the reduction of materials utilization along its production. In the same manner, this type of advances results on office furniture practices that are analogous with techniques used in Ecodesign, such as design fordisassembly and design for modularity, which also influences positively on the environmental performance of produced furniture. The suggested Ecodesign method consists of five steps: Identify products critical environmental areas; Set Ecodesign objectives; Generate Ecodesign information; Generate Ecodesign ideas; and Apply the Ecodesign ideas.